Peningkatan Hasil Belajar Peserta Didik Melalui Pembelajaran Berdiferensiasi Pada Mata Pelajaran Pendidikan Pancasila Kelas X.3 SMA Negeri 6 Palembang - Taufik Apriliani; Dahlia Dahlia; Sri Artati Waluyati (FKIP, Universitas Palangka Raya, 2024)
The research was conducted using collaborative classroom action research methods whose aim was to improve student learning outcomes in Civics subjects. This research was conducted by meeting the needs of students for learning styles, namely visual and auditory. This research was conducted in 2 research cycles consisting of 4 stages, namely planning, action implementation, observation, evaluation, and reflection. The research was conducted on class X.3 students of SMA Negeri 6 Palembang. With the results of the study showing that in the pre-cycle only 8 (27.58%) students achieved a completeness score, while 29 students (72.42%) had not completed, with an average score of 55.17. In cycle I, students experienced an increase in the number of students who completed 19 students (49.28%) while students who had not completed totaled 18 students (50.72%) with an average value of 66.55. Then in cycle II there was a very high increase compared to the previous cycle, namely students who had reached the KKM totaled 36 students (96.55%), while students who had not yet completed numbered 1 student (3.45%) with an average value of 80 This research shows that the application of differentiated learning can improve the learning outcomes of students in class X.3 SMA Negeri 6 Palembang.